Perlindungan Hukum Bagi Debitur dalam Sistem Pinjaman Financial Technology (Peer to Peer Lending) - Fajar Muazamsyah; Didik Suhariyanto; Puguh Aji Hari Setiawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of digital transformation technology requires the banking industry in the banking financial sector to innovate by combining digital technology with customer communication, a technology-based product called financial technology. This development is of course beneficial for the banking financial service system, but on the other hand it creates legal problems. The problems discussed in this study are First, what is the legal protection for debtors in the financial technology lending system (Peer to peer lending). Second, how is law enforcement in the financial technology lending system (peer to peer lending). The research method used is normative juridical law research with a statute approach and a conceptual approach. Legal materials in this study are divided into three sources of legal materials, namely primary, secondary and tertiary data. The results of the study show that debtors get legal protection, both preventive and repressive protection. Protection of preventive protection provided by the government with the aim of preventing before the occurrence of violations in the Peer to-peer lending financial technology transaction system. By providing a regulatory provision in both preventive and repressive protection efforts. The government's steps in preventive legal protection Peer to peer lending include service transparency, fraud prevention and the reliability of service systems and protection systems for personal data. Furthermore, regarding risk mitigation, system governance, education, limits on lending funds, First, repressive protection, handling of legal protection by the General court and by the Administrative Court in Indonesia. Second, government agencies which are administrative appeal institutions. Administrative sanctions in the form of fines, business restrictions, and revocation of activity permits. Law Enforcement in the Financial Technology Loan System through the application of administrative, civil and criminal law. Administrative law enforcement in the form of fines, restrictions on business activities and license revocation. Then, civil law enforcement through internal dispute resolution (IDR), Alternative Dispute Resolution (LAPS), as well as through general courts. While the enforcement of criminal law with criminal law procedures and criminal procedural law. On the other hand, the legal structure of OJK cooperates with law enforcement agencies in collaboration with Bank Indonesia, Polri, Kominfo and the Ministry of Cooperatives.